2012
DOI: 10.1002/hep.24752
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative liver function tests improve the prediction of clinical outcomes in chronic hepatitis C: Results from the hepatitis C antiviral long-term treatment against cirrhosis trial

Abstract: Risk for future clinical outcomes is proportional to the severity of liver disease in patients with chronic hepatitis C. We measured disease severity by quantitative liver function tests (QLFTs) to determine cutoffs for QLFTs that identified patients who were at low and high risk for a clinical outcome. Two hundred twenty seven participants in the Hepatitis C Antiviral Long-Term Treatment Against Cirrhosis (HALT-C) Trial underwent baseline QLFTs and were followed for a median of 5.5 years for clinical outcomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 53 publications
1
55
0
Order By: Relevance
“…An alternative and/or complementary diagnostic strategy is the use of tests that assess underlying functional liver reserve, whether using breath tests 134 or substrate clearance methods, 135 to predict clinical outcomes. One goal of these efforts is to establish their correlation with hepatic venous pressure gradient, since this measure clearly correlates with outcomes.…”
Section: Regulatory Challenges In Developing Novel Drugs For Hepatic mentioning
confidence: 99%
“…An alternative and/or complementary diagnostic strategy is the use of tests that assess underlying functional liver reserve, whether using breath tests 134 or substrate clearance methods, 135 to predict clinical outcomes. One goal of these efforts is to establish their correlation with hepatic venous pressure gradient, since this measure clearly correlates with outcomes.…”
Section: Regulatory Challenges In Developing Novel Drugs For Hepatic mentioning
confidence: 99%
“…Furthermore, it was thought to be a risk factor for the development of HCC [25]. However, it is unclear if thrombocytopenia per se is a risk factor for HCC development or just a phenomenon of more advanced liver disease, associated with an increased HCC incidence.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, thrombocytopenia, which is a hallmark of advanced liver disease and portal hypertension, has been associated with HCC development in cirrhotic patients with hepatitis C infection [24,25]. However, it is unclear if thrombocytopenia per se favors HCC or is just a marker of more severe liver disease [24].…”
Section: Introductionmentioning
confidence: 99%
“…Less than 10% of cirrhotic patients have normal values (100-110) with a PHM range of 40-99 in the rest [23,28,29] and the degree of abnormality correlates with clinical outcomes [28,29]. In the prospective HALT-C trial, PHM correlated with clinical outcomes over 7 years (46% outcomes with PHM \94 vs. 5% with [94) outperforming any combination of liver tests and histology [30]. Additional studies from the HALT-C trial have shown that preserved liver function is a better determinant of treatment success than is histology [31][32][33] and would support the possibility that these patients have a greater capacity to respond to therapy compared with cirrhotic patients with poor hepatic function.…”
Section: Discussionmentioning
confidence: 99%